Unravelling the hidden diversity of cave mycobiota in Thailand’s Satun Geopark - Satinee Suetrong; Sita Preedanon; Noppol Kobmoo; Charisa Srihom; Sayanh Somrithipol; Supicha Saengkaewsuk; Prasert Srikitikulchai; Anupong Klaysuban; Salilaporn Nuankaew; Charuwan Chuaseeharonnachai; Boonchuai Chainuwong; Chotika Muangsong; et al. (Scientific Reports, 2023)
Karst caves are distinctive ecosystems that have limited nutrients, darkness, low to moderate temperatures, and high moisture levels, which allow for a diverse range of fungal communities to thrive. Despite their significance, little is understood about the fungi found in karst caves in Thailand. In 2019, we studied the cultured mycobiota from five substrate types (air, water, rock, soil/sediment, and organic debris) in two karst caves (Le Stegodon and Phu Pha Phet Caves) of the Satun UNESCO Global Geopark, southern Thailand. A cumulative count of 829 distinct fungal morphological types was identified, encompassing 319 fungal culturable were observed. Based on preliminary analyses of the internal transcribed spacer (ITS) sequence using BLAST searches, the most common phylum among the fungal morphotypes was Ascomycota, harboring 282 species in 91 genera, 93.4% of which were distributed in the classes Eurotiomycetes, Sordariomycetes, and Dothideomycetes. The most common fungal genera identified in the two karst caves were Aspergillus, Penicillium, Cladosporium, Talaromyces, Xylaria, and Trichoderma, with 45, 41, 24, 14, 14, and 6 species identified, respectively. Discovering fungi in Thai karst caves highlights the extensive fungal diversity in the Satun UNESCO Global Geopark, implying undiscovered species, and emphasizing the need for comprehensive investigations in other unexplored Thai karst caves.
Keywords: Building materials and conservation; Plant Pathogens and Fungal Diseases; Slime Mold and Myxomycetes Research